A Case study on the changes in production system of a medium-scale garment manufacturer during the COVID-19 pandemic - Manabat, Jecel Marie B. (Quezon City College of Home Economics, University of the Philippines Diliman, 2021)
The COVID-19 pandemic has had a grave impact on the global supply chain of the garment industry, global demad for garments, and production processes of garment manufacturers (Jacson et al., 2020). Various regulations that has affected manufacturers have been implemented. In order to continue their operations, companies are mandated to ensure physical distancing, limit the amount of workforce, and require face masks, among other minimum health requirements. This case study proposes to analyze the management strategies of a selected garment manufacturing company in response to the effects of COVID-19 pandemic. it could serve as basis for government policies and programs to help manufacturers recover from the pandemic. It may also be used in determining the best system in terms of material handling, equipment, human resources, and production processes, both prior to and during the COVID-19 pandemic was used to propose a research design. An interview guide was developed which consists of four major sections - (1) Company Profile; (2) Material Handling; (3) Production Process; and (4) Human Resources and Equipment. A descriptive cross-comparison analysis of the production system before and during the pandemic is suggested to analyze the what production management strategies were implemented by the selected manufacturing company. A recommendation on data analysis, considering possible themes for discussion are found in the concluding chapter.
Thesis Classification: F (Available for Public)
Thesis
Includes bibliographical references and appendices.
Keywords: Manufacturing processes -- Philippines; Clothing trade -- Philippines; Production management -- Philippines; COVID-19 Pandemic, 2020- -- Philippines